Hey there! :)
Answer:
(g-f)(10) = 279/10.
Step-by-step explanation:
Given:
[tex]f(x) = x^{-1}[/tex]
and
[tex]g(x) = 2x + 8[/tex]
Begin by solving for (g-f) by subtracting f(x) from g(x):
[tex](g-f)(x) = 2x + 8 - x^{-1}[/tex]
Substitute in 10 for x in the equation to solve this problem:
[tex](g-f)(10) = 2(10) + 8 - 10^{-1}[/tex]
Simplify:
[tex](g-f)(10) = 20 + 8 - \frac{1}{10}[/tex]
Create a common denominator to simplify further:
[tex](g-f)(10) = \frac{200}{10}+ \frac{80}{10} - \frac{1}{10}[/tex]
[tex](g-f)(10) = \frac{279}{10}[/tex]
Therefore:
(g-f)(10) = 279/10.